2014
DOI: 10.1111/maec.12162
|View full text |Cite
|
Sign up to set email alerts
|

Exploring composition and behaviour of fish fauna by in situ observations in the Bari Canyon (Southern Adriatic Sea, Central Mediterranean)

Abstract: Canyons play a fundamental role in enhancing the abundance and diversity of marine organisms through the transport of organic matter and food resources, the presence of complex physical habitats and the absence of trawl fishing. During four baited lander deployments carried out in the Bari Canyon (Southern Adriatic Sea, Central Mediterranean), at depths of 443–788 m, about 43 h of video records were taken, for a total of 619,200 video frames. A total of 12 benthopelagic fish species (five chondrichthyes and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 61 publications
4
34
1
Order By: Relevance
“…The association of C. conger, P. bogaraveo, and H. dactylopterus with the cold-water coral M. oculata in the catch also confirms the preferred distribution of these species within the coral habitat, previously documented in the SML CWC province (D'Onghia et al, , 2011(D'Onghia et al, , 2012. Moreover, the most frequent observations of C. conger and H. dactylopterus in the present study using both baited lander and longline could be due to a preferential distribution of these fishes in a complex and heterogeneous habitat (D'Onghia et al, 2014;Fabri et al, 2014).…”
Section: Actinopterygiisupporting
confidence: 70%
See 4 more Smart Citations
“…The association of C. conger, P. bogaraveo, and H. dactylopterus with the cold-water coral M. oculata in the catch also confirms the preferred distribution of these species within the coral habitat, previously documented in the SML CWC province (D'Onghia et al, , 2011(D'Onghia et al, , 2012. Moreover, the most frequent observations of C. conger and H. dactylopterus in the present study using both baited lander and longline could be due to a preferential distribution of these fishes in a complex and heterogeneous habitat (D'Onghia et al, 2014;Fabri et al, 2014).…”
Section: Actinopterygiisupporting
confidence: 70%
“…Most of these species have been recently recorded in the Bari Canyon by in situ observations with an ROV and a baited lander (Angeletti et al, 2014;D'Onghia et al, 2014) and the vertical distribution of P. bogaraveo and H. dactylopterus in this area has also been updated (D'Onghia et al, 2014). M. poutassou, M. dypterygia, and S. elongata previously recorded from the southern Adriatic Sea (Ungaro et al, 1999) are here reported for the first time from Bari Canyon.…”
Section: Actinopterygiimentioning
confidence: 71%
See 3 more Smart Citations